TREN PEMIKIRAN INTELEKTUAL MUSLIM KONTEMPORER DI TIMUR TENGAH PASCA-DIFITISME 1967 - Yoyo, Yoyo (Sekolah Pascasarjana UGM, 2012)
This article is an effort to make a clear map on contemporary Muslim intellectuals in the Middle East after the Arab defeat in 1967. The Six-Day War took place in June 1967 was a disaster for the Arab world. It ended the ideology of Pan-Arab nationalism and encouraged the rise of four compating self-criticism ideologies: Marxism, Liberalism, Fundamentalism and Nationalism. The four ideologies have their own particular responses and solutions to the Arab crisis. The result of this research shows that Islamic fundamentalism is still the strongest ideology compared to the secular ideologies. The Arab Spring in 2011 proved the fact and paved a way for the Islmists to become dominant in the political arena, as recently shown in Egypt. The other Islamist militant groups, such as Jamaâah Islamiyyah are now more free to promote the implementation of Islamic syariâah.